Problematics of Single Parenting of Their Biological Children and Its Consequences From the Perspective of Islamic Law (Case Study at the Office of the Ministry of Religious Affairs, Palu City) - Nadya Alwi; Lukman S. Thahir; Gasim Yamani (State Islamic University Datokarama Palu, 2025)
This study analyzes the challenges of single mother parenting and its legal consequences from an Islamic law perspective at the Office of the Ministry of Religious Affairs in Palu City. Using a qualitative approach, data were gathered through interviews, observation, and documentation, then analyzed via reduction, display, and conclusion drawing. The results reveal that single mothers face significant emotional and economic shifts, including limited time with children due to increased work demands. To compensate, these mothers adopt dual roles as both provider and nurturer. The findings indicate that while single parents encounter obstacles in child discipline, they predominantly implement democratic parenting. From an Islamic law perspective, this democratic approach is considered the most suitable for child development. The study recommends that religious institutions intensify family law outreach and counseling specifically for single mothers. Furthermore, cross-sector collaboration between the Ministry of Religious Affairs, social services, and child protection agencies is essential to establish a robust support system for single-parent households.